2017
DOI: 10.3168/jds.2016-11970
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with postpartum subclinical hypocalcemia in dairy cows

Abstract: Our study objectives were to evaluate the association of prepartum plasma Mg concentrations with subclinical hypocalcemia (SCH) classification at parturition and to evaluate the association of other cow-level risk factors with SCH classification at calving or at 2 d in milk (DIM). A total of 301 animals from 2 dairy herds located in New York were enrolled in a cohort study. Blood samples were collected at approximately 1 wk before the expected calving date, within 4 h of calving, and at 2 DIM. Prepartum sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 26 publications
5
44
4
2
Order By: Relevance
“…At 3 DIM, BCS following a 5-point scale with quarter-point increments (Ferguson et al, 1994) and locomotion score (LS) following a 5-point scale (Sprecher et al, 1997) were performed by the first author. Description of the herds and rations fed in the prepartum and postpartum periods can be found in Neves et al (2017).…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…At 3 DIM, BCS following a 5-point scale with quarter-point increments (Ferguson et al, 1994) and locomotion score (LS) following a 5-point scale (Sprecher et al, 1997) were performed by the first author. Description of the herds and rations fed in the prepartum and postpartum periods can be found in Neves et al (2017).…”
Section: Experimental Designmentioning
confidence: 99%
“…To date, there is no consensus in the literature as to how (i.e., what cut point to use) and when to classify SCH in relation to parturition, as blood Ca testing is more likely to be applied by dairy producers and consultants if a specific time point relative to parturition can be better identified; this is further complicated by the fact that the appropriate cut point or DIM of blood Ca assessment could differ based on the outcome measured. In an earlier study, our group was able to demonstrate that the risk factors associated with a suboptimal Ca concentration state in the early postpartum period are different depending on the time of blood Ca assessment (i.e., within 4 h of parturition and at 2 DIM; Neves et al, 2017). This sug-gests that timing of blood sample collection relative to parturition for blood Ca assessment may be an important factor to take into account when determining the association between SCH and downstream outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Hypocalcaemia impacts health, future milk production, and reproductive performance and has been demonstrated to be linked with compromised immune function; cows with lower blood Ca concentrations within the first day after calving were more likely to have retained placenta and resulting metritis, and mastitis [50]. In addition, hypocalcaemia is also associated with metabolic diseases such as left displaced abomasum, ketosis and fatty liver [51,52].…”
Section: Hypocalcaemia (Milk Fever)mentioning
confidence: 99%
“…Some found negative associations with indicators of reproductive performance (Martinez et al, 2012(Martinez et al, , 2016Caixeta et al, 2017), whereas others reported no association (Chamberlin et al, 2013;Gild et al, 2015;Rodríguez et al, 2017). These discrepancies could partly be the result of differences in the study design (i.e., timing of diagnosis and cut-point used; Neves et al, 2017). No consensus exists as to when and how to objectively assess SCH, and this lack of standardization of SCH classification may affect our ability to establish associations between SCH and fertility (Neves et al, 2018).…”
Section: Associations Of Subclinical Hypocalcemia With Fertility In Amentioning
confidence: 99%